Permeability Correction in Low-Permeability Soils Using a Seepage Force Consolidation Test - Xie, Yao; Chen, Ping-Shan; Gu, Ren-Guo; Wang, Jing; Gao, Kang; Fang, Ying-Guang (Geotechnical and geological engineering, 2025)
Seepage force consolidation induced by leakage in underground structures may significantly alter soil permeability, and redistribute pore water pressure and effective stress, thereby increasing operational risks of underground structures. This study focuses on revealing the key mechanism by which seepage force consolidation governs permeability coefficient variations in low-permeability soils. Seepage consolidation experiments were conducted under varying hydraulic gradients using a self-developed apparatus for high-hydraulic-head seepage consolidation; experimental results demonstrate that seepage force consolidation causes progressive reduction in soil void ratio along the seepage direction, substantially altering its permeability coefficient. Mercury Intrusion Porosimetry (MIP) tests and analytical solutions for seepage force consolidation were employed to further elucidate the physical mechanism controlling permeability evolution. A soil permeability coefficient correction method was established based on a multi-layer seepage model, quantifying how seepage-consolidation coupling affects soil permeability, and enabling precise estimation of equivalent permeability coefficients for in situ soils. Limitations of conventional seepage models neglecting non-uniform consolidation effects induced by seepage forces were overcome, providing theoretical frameworks and practical methodologies for more accurate assessment of actual water pressure load distributions on underground structures, refinement of seepage testing methods for low-permeability soils, and enhanced reliability in engineering safety predictions under complex seepage environments.